Factors affecting forage stand establishment - R.M. Sulc (Scientia Agricola, 1998)
Significant advances have been made in our knowledge of forage seed physiology, technology, and stand establishment practices; however, stand establishment continues to be one of the most common production problems affecting forage crops in the USA. There is a need for research on stand establishment of forage crops under abiotic and biotic stress. Although the forage seed industry produces and markets seed of high quality, new methods of assessing seed vigor are needed and their use should be expanded in the industry to enable matching seed lot performance to specific environmental conditions where performance can be maximized. Seed treatment and seed coating are used in the forage seed industry, and studies have shown they are of benefit in some environments. There is an increase in no-tillage seeding of forage crops, but improvements in the no-tillage planting equipment are needed to make them better suited to small seeds. Other recent developments in seeding techniques include broadcasting seed with dry granular and fluid fertilizers, which improves the efficiency of the seeding operation.